The application of the differential quadrature method based on a piecewise polynomial to the vibration analysis of geometrically nonlinear beams - Krowiak, Artur (Computer Assisted Methods in Engineering and Science, 2008)
The paper deals with the application of the differential quadrature method based on a piecewise polynomial to the nonlinear vibration analysis of beams. The initial-boundary-value problem is solved to study the computational stability of the method. The results are compared with those, obtained by the conventional differential quadrature. The effects of the spline degree, the number of nodes and the distribution of sampling points on the convergence and stability is also presented. The nonlinear free vibration analysis is carried out to verify the accuracy of the method.